Advanced MRI Techniques for Muscle Imaging - Kalia, Vivek; Leung, Doris G.; Sneag, Darryl B.; Grande, Filippo Del; Carrino, John A. (Seminars in Musculoskeletal Radiology, 2017)
Advanced magnetic resonance imaging (MRI) techniques can evaluate a wide array of muscle pathologies including acute or chronic muscle injury, musculotendinous response to injury, intramuscular collections and soft tissue masses, and others. In recent years, MRI has played a more important role in muscle disease diagnosis and monitoring. MRI provides excellent spatial and contrast resolution and helps direct optimal sites for muscle biopsy. Whole-body MRI now helps identify signature patterns of muscular involvement in large anatomical regions with relative ease. Quantitative MRI has advanced the evaluation and disease tracking of muscle atrophy and fatty infiltration in entities such as muscular dystrophies. Multivoxel magnetic resonance spectroscopy (MRS) now allows a more thorough, complete evaluation of a muscle of interest without the inherent sampling bias of single-voxel MRS or biopsy. Diffusion MRI allows quantification of muscle inflammation and capillary perfusion as well as muscle fiber tracking.
Keywords: MRI; muscle; quantitative MRI; MR spectroscopy; diffusion imaging